Comparison of body composition and adipokine levels between thin and normal‐weight prepubertal children - Jadwiga Ambroszkiewicz; Joanna Gajewska; Katarzyna Szamotulska; Grażyna Rowicka; Witold Klemarczyk; Magdalena Chełchowska (Brazilian Society of Pediatrics, 2017)
Objective: Thinness can have substantial consequences for child development and health. Adipokines, including leptin and adiponectin, play a significant role in the regulation of important metabolic functions. The aim of this study was to investigate associations between body composition and serum leptin and adiponectin levels in thin and normal‐weight children. Methods: The authors examined 100 healthy prepubertal children, who were divided into two subgroups: thin (n = 50) and normal‐weight children (n = 50). Body composition was assessed by dual‐energy X‐ray absorptiometry. Serum concentrations of adipokines were determined by immunoenzymatic assays. Results: Thin children had a similar body height but significantly lower (p < 0.0001) body weight, body mass index, fat mass, lean mass, and bone mineral content compared with normal‐weight children. Serum concentrations of leptin were about 2‐fold lower (p < 0.0001) in thin vs. normal‐weight subjects. Serum levels of total adiponectin, adiponectin multimers, and soluble leptin receptor (sOB‐R) were similar in both groups. The leptin/soluble leptin receptor ratio and leptin/adiponectin ratios were lower (p < 0.0001) in thin vs. normal‐weight children. In both groups of children, it was found that body composition parameters were positively related with leptin but not with adiponectin levels. Additionally, bone mineral content was positively related with body mass index, fat mass, lean mass, and leptin level in thin and normal‐weight children. Conclusions: Prepubertal thin children have disturbances in body composition and adipokine profile. Early recognition of thinness and determination of body composition parameters and adipokine levels can be useful in medical and nutritional care of thin children for the optimization of bone mineral accrual.